2004
DOI: 10.1007/s11661-004-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

Charpy-impact-toughness prediction using an “effective” grain size for thermomechanically controlled rolled microalloyed steels

Abstract: Thermomechanically controlled rolling of steel plate can involve substantial straining in the intercritical temperature region, which may result in the final ferrite grains not fully recrystallizing, and, hence, the presence of low-angle grain boundaries. It is shown in this article that a Nb-microalloyed thermomechanically controlled rolled (TMCR) steel can contain a high proportion of low-angle grain boundaries (the extent depending on the thermomechanically controlled rolling schedule) and that during tough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 10 publications
0
47
0
Order By: Relevance
“…For polygonal ferrite these low angle boundaries result from the combination of the K-S orientation relationship and a variant selection during austenite transformation (Bengochea et al, 1998, Novillo et al, 2005. Consequently, even for simple ferrite microstructures, optically measured grain sizes can be significantly different from those obtained by EBSD (Bhattacharjee et al, 2004) unless the appropriate threshold angle and correlations are applied (Iza-Mendia and Gutiérrez, 2013).…”
Section: Boundary Misorientation Distributions and Grain Sizementioning
confidence: 99%
See 1 more Smart Citation
“…For polygonal ferrite these low angle boundaries result from the combination of the K-S orientation relationship and a variant selection during austenite transformation (Bengochea et al, 1998, Novillo et al, 2005. Consequently, even for simple ferrite microstructures, optically measured grain sizes can be significantly different from those obtained by EBSD (Bhattacharjee et al, 2004) unless the appropriate threshold angle and correlations are applied (Iza-Mendia and Gutiérrez, 2013).…”
Section: Boundary Misorientation Distributions and Grain Sizementioning
confidence: 99%
“…Cleavage happens usually on {001} ferrite planes and the crack deflects at boundaries that can be considered as misorientation dependent energy barriers for propagation. The value of D was traditionally expressed as an optical ferrite boundary mean linear intercept, but EBSD has revealed that, even for ferrite-pearlite obtained after thermomechanical treatments (Bengochea et al, 1998, Novillo et al, 2005, Bhattacharjee et al, 2004 a relatively high density of low angle boundaries develops. The situation becomes more complex for bainite or martensite.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture toughness is determined by the amount of the work of plastic deformation in the fracture zone, which depends on the type of the microstructure formed during thermomechanical processing of the initial hot-rolled sheet [24][25][26]. Unlike other steels, the pipeline steels have a well-defined ratio of strength, ductility and fracture toughness, which is specified by the thermomechanical processing scheme [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate design of the chemical composition together with a thermomechanically controlled process (TMCP) contribute to the achievement of effective microstructures and textures, ensuing improved mechanical properties. [6,10] It has been largely reported in the literature that mechanical properties of pipeline steels like yield strength and toughness are strongly affected by thermo-mechanical controlled processing. The properties are mainly dependent on the rolling temperatures, the finish cooling temperature and the cooling rate on the runout table after hot rolling.…”
mentioning
confidence: 99%
“…[11] However, these mechanical properties often display high anisotropy and it is not well understood to which microstructural or crystallographic elements this can be attributed. Mechanical anisotropy has been extensively studied by analyzing the effect of microstructural parameters [4][5][6][7] and by analyzing the effect of texture. [8][9][10] Nevertheless, the effect of texture and microstructure on the anisotropy in the ductileto-brittle transition region (DBTR) is not yet well known.…”
mentioning
confidence: 99%